Regeneration method of methanol cracking / reforming hydrogen production copper-based catalyst

Through regeneration procedures such as acid treatment and precipitation conversion, the waste copper-based catalyst is regenerated into a highly reactive regenerated copper-based catalyst, solving the problems of catalyst activity attenuation and environmental pollution, and realizing the reduction of the cost of recycling catalysts and hydrogen production.

CN119524877AInactive Publication Date: 2025-02-28ANHUI POLYTECHNIC UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510106189.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The activity of existing copper-based catalysts is attenuated during use, resulting in the need to replace new catalysts, which increases the cost of hydrogen production, and the scrap catalysts are polluted to the environment and have high disposal costs.

Method used

Through regeneration procedures such as acid treatment and precipitation conversion, the waste copper-based catalyst is regenerated into a highly reactive regenerated copper-based catalyst, including crushing, acid treatment, activation, precipitation conversion, separation, material washing, calcining and granulation.

Benefits of technology

The activity and performance of the catalyst are improved, allowing the catalyst to be recycled, reducing the cost of hydrogen production, and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524877A_ABST
    Figure CN119524877A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper-based catalysts, and discloses a regeneration method of a methanol cracking / reforming hydrogen production copper-based catalyst, which comprises the following steps: crushing and grinding a waste copper-based catalyst into powder; carrying out acid treatment on the powder by using a mixed acid of organic acid and inorganic acid to obtain a mixed solution; adding a precipitant and a pH regulator into the mixed solution, and carrying out active substance conversion; meanwhile, metal salt auxiliary materials and auxiliaries are added, so that the comprehensive performance of the catalyst is improved; after the reaction is finished, carrying out solid-liquid separation to obtain a solid catalyst coarse material; washing with deionized water to obtain a solid catalyst washing material; and calcining to obtain the finished product powder regenerated catalyst. According to the regeneration method of the methanol cracking / reforming hydrogen production copper-based catalyst, the waste copper-based catalyst is used as a raw material, and the high-activity regenerated copper-based catalyst is prepared through regeneration procedures such as acid treatment and precipitation conversion, so that the performance of the catalyst is improved, and the catalyst is recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-based catalysts, and in particular to a method for regenerating a copper-based catalyst for producing hydrogen through methanol cracking / reforming. Background Art

[0002] As energy demand grows and renewable resources become limited, scientists from all over the world are focusing on exploring new energy sources that can replace existing energy sources and provide sustainable supply. Among them, hydrogen energy is an ideal clean energy source, and its energy release per unit mass is better than that of petrochemical energy such as natural gas, making it one of the ideal new energy sources worth exploring.

[0003] Methanol cracking / reforming (MSR) to produce hydrogen has a high research value. At present, methanol cracking / reforming (MSR) hydrogen production technology is mature and has diversified application sites. It has become one of the mainstream technologies for hydrogen production. In the hydrogen production process, copper-based catalysts are mainly used, mainly because their price is lower than that of precious metal catalysts and their activity is higher. Therefore, copper-based catalysts are the most commonly used in this hydrogen production technology. However, with the urgency of energy demand, the scale and production capacity of methanol hydrogen production have also increased year by year, and the amount of copper-based catalysts has also increased accordingly. Among them, the amount and price of production raw materials are inevitably affected, which indirectly leads to the uncontrollable cost of hydrogen production. From the current point of view, there is an increasing trend; in addition, the deeper the industrialization of hydrogen production is, the more copper-based catalysts are used. After a certain period of use, the activity of the catalyst gradually decays and degrades with the increase of operating time, sintering or active point burial occurs, and even poisoning and inactivation occur. New catalysts need to be replaced, which is expensive, and scrapped catalysts have certain pollution to the environment, and the cost of scrapping disposal is relatively high. Therefore, it is necessary to recycle it as much as possible, which is not only conducive to the stable supply of copper-based catalysts in the market, but also will achieve effective pressure reduction in environmental governance. Therefore, it is of great significance to study a method for regenerating copper-based catalysts for hydrogen production from waste methanol cracking / reforming. Summary of the invention

[0004] The purpose of the present invention is to provide a method for regenerating a copper-based catalyst for hydrogen production by cracking / reforming of methanol. Using waste copper-based catalysts as raw materials, a high-activity regenerated copper-based catalyst is prepared through regeneration procedures such as acid treatment and precipitation conversion, which not only improves the performance of the catalyst but also allows the catalyst to be recycled.

[0005] To achieve the above object, the present invention provides a method for regenerating a copper-based catalyst for hydrogen production by methanol cracking / reforming, comprising the following steps: Step 1, crushing the waste copper-based catalyst: crushing and grinding the waste copper-based catalyst into powder; Step 2, acid treatment: using a mixed acid solution of an organic acid and an inorganic acid to acid-treat the powder in step 1 to obtain a mixed solution; Step 3, activation enhancement: adding metal salt auxiliary materials and additives to the mixed solution of step 2 to improve the comprehensive performance of the catalyst; Step 4, precipitation conversion: while step 3 is being carried out, a precipitant and a pH adjuster are added to convert the active substance; Step 5, separation: after the reaction of step 3 and step 4 is completed, solid-liquid separation is performed to obtain a solid catalyst crude material; Step 6, washing: washing the solid catalyst crude material with deionized water until the pH value is 6-8 to obtain a solid catalyst washing material; Step 7, calcination: calcining the solid catalyst wash material to obtain a finished powder regeneration catalyst; Step 8, granulation and packaging: the finished powder regenerated catalyst is further granulated to prepare granular catalysts of different sizes to obtain the regenerated finished copper-based catalyst, which is then packaged.

[0006] Furthermore, in step 1, the particle size of the powder is 80-1000 mesh.

[0007] Furthermore, in step 2, the organic acid is one or more of oxalic acid, citric acid, acetic acid, EDTA, glycolic acid, and formic acid; the inorganic acid is one or more of nitric acid and hydrochloric acid; and the molar ratio of the inorganic acid to the organic acid is inorganic acid: organic acid = 3-5:1.

[0008] Furthermore, in step 2, the ratio of the powder to the mixed acid solution is powder: mixed acid solution = 1 kg: 3-6 L, and the mixed acid solution contains 50-60 kg of acid per 300 L of deionized water.

[0009] Furthermore, in step 2, the acid treatment conditions are a temperature of 50-90° C., stirring, and a reaction time of 10-24 hours.

[0010] Furthermore, in step 3, the precipitant is one or more of sodium carbonate and sodium bicarbonate, and the pH adjuster is one or more of sodium hydroxide and potassium hydroxide.

[0011] Furthermore, in step 3, the reaction conditions are a temperature of 40-100° C. with stirring, a pH of 9.5-11, and a reaction time of 6-24 h.

[0012] Furthermore, in step 4, the metal salt auxiliary material is one or more nitrates containing manganese, zirconium, zinc, barium, copper, aluminum or magnesium; the auxiliary agent is one or more of P123, F127, PEG600; the molar ratio of Cu to the metal salt auxiliary material and the auxiliary agent in the copper-based catalyst is Cu: metal salt auxiliary material: auxiliary agent = 1: 0.01~0.08: 0~0.015.

[0013] Furthermore, in step 7, the calcination conditions are to increase the temperature from room temperature to the calcination temperature at a heating rate of 8-15°C / min, and keep the temperature for 120-200 min, and then cool naturally; the calcination temperature is 320-420°C.

[0014] The invention also discloses a copper-based catalyst for methanol cracking / reforming to produce hydrogen, which is prepared by the above regeneration method.

[0015] The advantages and positive effects of the regeneration method of a copper-based catalyst for methanol cracking / reforming to produce hydrogen described in the present invention are: 1. The regeneration method of the present invention is simple and easy to implement. The main reaction is in the acid treatment and precipitation conversion stages. After the acid dissolves the catalyst, the precipitant, metal auxiliary materials and other additives are directly added, and the reaction is completed at one time. Then, the solid-liquid separation is performed and the next step is entered. The main device involved in the overall process is a conventional reaction device, which has low equipment hardware requirements, simple operation and relatively low regeneration cost.

[0016] 2. The acid treatment of the present invention adopts a mixed acid of inorganic acid and organic acid, which has a good dissolving effect. The addition of precipitants, pH regulators, metal salt adjuvants and other additives can easily dissolve and remove the ineffective components of the waste catalyst, and it is easier to produce complex basic copper-zinc-aluminum carbonate precipitation. During calcination, a faster heating rate is used to quickly decompose the basic copper-zinc-aluminum carbonate to release a relatively large amount of small molecular gases such as CO2 and H2O. The gas impact explosion makes the copper-zinc-aluminum oxide produced smaller and more uniform. The small-sized catalyst particles provide a larger active specific surface for the catalyst, which will help to improve the overall activity of the catalyst.

[0017] 3. In the conversion precipitation reaction stage, the present invention adds metal salt auxiliary materials, including nitrates or chlorides of the original elements of the catalyst, including manganese, zirconium, zinc, barium, copper, aluminum, and magnesium, or water-soluble organic salts containing carbon, hydrogen, and oxygen. The introduction of a small amount of other metal salts (excluding the metal elements of the waste catalyst itself) is beneficial to improving the temperature resistance, stability, activity, etc. of the catalyst.

[0018] 4. In the conversion precipitation reaction stage of the present invention, other additives are added, including P123, F127, and PEG600. The addition of additives can make the catalyst precursor precipitate particles produced by the reaction smaller and more uniform, and then the copper-zinc-aluminum oxide particles produced during calcination and decomposition are smaller and more uniform, which will have a good effect on improving the catalyst activity.

[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the regeneration process of waste copper-based catalysts in an embodiment of the present invention; Figure 2are the activity test results of the waste copper-based catalyst before and after regeneration in the embodiments of the present invention, wherein A is the activity of the waste copper-based catalyst before regeneration, B is the activity of the waste copper-based catalyst after regeneration in Embodiment 1, C is the activity of the waste copper-based catalyst after regeneration in Embodiment 2, D is the activity of the waste copper-based catalyst after regeneration in Embodiment 3, and E is the activity of the waste copper-based catalyst after regeneration in Embodiment 4; Figure 3 : are XRD spectra of the waste copper-based catalyst before and after regeneration in the embodiments of the present invention, wherein A is the XRD spectrum of the waste copper-based catalyst before regeneration, B is the XRD spectrum of the waste copper-based catalyst after regeneration in Embodiment 1, C is the XRD spectrum of the waste copper-based catalyst after regeneration in Embodiment 2, D is the XRD spectrum of the waste copper-based catalyst after regeneration in Embodiment 3, and E is the XRD spectrum of the waste copper-based catalyst after regeneration in Embodiment 4; Figure 4 This is the Mapping test result after the waste copper-based catalyst is regenerated in Example 3 of the present invention; Figure 5 The adsorption test results of the waste copper-based catalyst before and after regeneration in Example 4 of the present invention, wherein A is the adsorption test result of the waste copper-based catalyst before regeneration, and B is the adsorption test result of the waste copper-based catalyst after regeneration; Figure 6 The stability test results of the waste copper-based catalyst after regeneration in Example 4 of the present invention are shown. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0022] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0023] Unless otherwise specified, the experimental materials and reagents used in the following examples can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.

[0024] Unless otherwise defined or described, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0025] The process flow chart of a method for regenerating a copper-based catalyst for hydrogen production by methanol cracking / reforming in the present invention is as follows: Figure 1As shown, the following examples are described by taking waste copper-based catalyst as raw material to prepare copper-zinc-aluminum catalyst.

[0026] Example 1 A method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen comprises the following steps: Step 1, weigh 100 kg of waste copper-based catalyst, crush it and grind it into powder with a particle size of 200 mesh.

[0027] Step 2, mix the acid with deionized water, measure 300L of deionized water and add it to the reactor, then add 40kg of nitric acid and 10kg of oxalic acid in sequence, start stirring to fully dissolve and mix; add the ground waste catalyst powder to the mixed acid solution, stir and dissolve in the reactor for 12 hours, and control the temperature at 60°C.

[0028] The metal salt auxiliary materials are Cu(NO3)2, Zn(NO3)2 and Al(NO3)3, according to the molar ratio of Cu(NO3)2:Zn(NO3)2:Al(NO3)3 =3:1:1, and the total mass added is about 10kg. The three nitrates are weighed respectively according to the molar ratio.

[0029] Step 3, add the weighed three nitrates into the reactor, mix them thoroughly with the dissolved waste catalyst, control the temperature at 60°C, and continue stirring for another 2 hours.

[0030] Weigh 125 kg of sodium carbonate and add it to the reactor within 1.5 hours. At the same time, slowly add 5 mol / L sodium hydroxide solution, control the pH to 9.8-10.5, control the temperature to 60°C, and continue stirring and precipitating for 12 hours. Step 4, after the precipitation conversion is completed, the temperature is lowered to below 40°C, solid-liquid separation is performed, and centrifugal separation is performed, and the separated liquid is collected.

[0031] Step 5, after the solid is collected, it is washed in a washing tank, 300L of deionized water is added for stirring and washing, and then centrifuged; the washing is repeated 2-3 times, and 0.5-1% oxalic acid solution can be appropriately added for neutralization washing in the last time, and the solid material is washed until the pH is neutral.

[0032] Step 6: Load the solid material into the calcination tray and move it into the calcination furnace. Set the calcination temperature to 400°C, increase the temperature by 10°C / min, maintain 400°C for 120min, and cool it down to room temperature naturally before taking it out of the furnace.

[0033] Step 7, granulate the calcined powder into required specifications and sizes according to the needs of different application sites, and then measure and package it.

[0034] Example 2 A method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen comprises the following steps: Step 1, weigh 50 kg of waste copper-based catalyst, crush it and grind it into powder with a particle size of 140 mesh.

[0035] Step 2, mix the acid solution with deionized water, measure 150L of deionized water and add it into the reactor, then add 20kg of nitric acid and 6kg of acetic acid in sequence, start stirring to fully dissolve and mix; add the ground waste catalyst powder into the mixed acid, stir and dissolve it in the reactor for 10 hours, and control the temperature at 80°C.

[0036] The metal salt auxiliary materials are Cu(NO3)2, Zn(NO3)2 and Al(NO3)3, according to the molar ratio of Cu(NO3)2:Zn(NO3)2:Al(NO3)3 =2:1:1, and the total mass added is about 4.5kg. The three nitrates are weighed respectively according to the molar ratio.

[0037] Step 3, add the weighed three nitrates into the reactor, mix them thoroughly with the dissolved waste catalyst, control the temperature at 80°C, and continue stirring for another 1 hour.

[0038] Weigh 60 kg of sodium carbonate and add it to the reactor within 1.5 hours. At the same time, slowly add 5 mol / L sodium hydroxide solution, control the pH to 10-10.5, control the temperature to 80°C, and continue stirring and precipitating for 10 hours.

[0039] Step 4, after the precipitation conversion is completed, the temperature is lowered to below 40°C, solid-liquid separation is performed, and centrifugal separation is performed, and the separated liquid is collected.

[0040] Step 5, after the solid is collected, it is washed in a washing tank, 120L of deionized water is added for stirring and washing, and then centrifuged; the washing is repeated 2-3 times, and 0.5-1% nitric acid solution can be appropriately added for neutralization in the last washing, and the solid material is washed until the pH is neutral.

[0041] Step 6: Load the solid material into the calcination tray and move it into the calcination furnace. Set the calcination temperature to 350°C, increase the temperature by 15°C / min, maintain 350°C for 140min, and cool naturally to room temperature before taking it out of the furnace.

[0042] Step 7, granulate the calcined powder into required specifications and sizes according to the needs of different application sites, and then measure and package it.

[0043] Example 3 A method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen comprises the following steps: Step 1, weigh 100 kg of waste copper-based catalyst, crush it and grind it into powder with a particle size of 200 mesh.

[0044] Step 2, mix the acid with deionized water, measure 300L of deionized water and add it into the reactor, then add 40kg of nitric acid and 10kg of citric acid in sequence, start stirring to fully dissolve and mix; add the ground waste catalyst powder into the mixed acid, stir and dissolve in the reactor for 12 hours, and control the temperature at 60°C.

[0045] The metal salt auxiliary materials are Cu(NO3)2, Zn(NO3)2, Al(NO3)3 and Ba(NO3)2, according to the molar ratio of Cu(NO3)2:Zn(NO3)2:Al(NO3)3 =3:1:1, and the total mass added is about 10kg. The three nitrates are weighed respectively according to the molar ratio.

[0046] Then weigh 8 kg of barium nitrate and 0.5 kg of PEG600.

[0047] Step 3, add the weighed four nitrates and PEG600 into the reactor, mix them thoroughly with the dissolved waste catalyst, control the temperature at 80°C, and continue stirring for another 2 hours.

[0048] Weigh 125 kg of sodium carbonate and add it to the reactor within 1.5 hours. At the same time, slowly add 5 mol / L sodium hydroxide solution, control the pH to 9.8-10.5, control the temperature to 80°C, and continue stirring and precipitating for 12 hours.

[0049] Step 4, after the precipitation conversion is completed, the temperature is lowered to below 40°C, solid-liquid separation is performed, and centrifugal separation is performed, and the separated liquid is collected.

[0050] Step 5, after the solid is collected, it is washed in a washing tank, 300L of deionized water is added for stirring and washing, and then centrifuged; the washing is repeated 2-3 times, and 0.5-1% nitric acid solution can be appropriately added for neutralization washing in the last time, and the solid material is washed until the pH is neutral.

[0051] Step 6: Load the solid material into the calcination tray and move it into the calcination furnace. Set the calcination temperature to 400°C, increase the temperature by 10°C / min, maintain 400°C for 120min, and cool it down to room temperature naturally before taking it out of the furnace.

[0052] Step 7, granulate the calcined powder into required specifications and sizes according to the needs of different application sites, and then measure and package it.

[0053] Example 4 A method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen comprises the following steps: Step 1, weigh 50 kg of waste copper-based catalyst, crush it and grind it into powder with a particle size of 140 mesh.

[0054] Step 2, mix the acid solution with deionized water, measure 150L of deionized water and add it into the reactor, then add 25kg of nitric acid and 5kg of acetic acid in sequence, start stirring to fully dissolve and mix; add the ground waste catalyst powder into the mixed acid, stir and dissolve it in the reactor for 10 hours, and control the temperature at 70°C.

[0055] The metal salt auxiliary materials are Cu(NO3)2, Zn(NO3)2, Al(NO3)3 and Mn(NO3)2 at the ratio of Cu(NO3)2:Zn(NO3)2:Al(NO3)3=3.5:1:1 (molar ratio). The total mass added is about 4kg. The three nitrates are weighed respectively according to the molar ratio.

[0056] Then weigh 6kg of manganese nitrate and 0.2kg of F127.

[0057] Step 3, add the weighed four nitrates and F127 into the reactor, mix them thoroughly with the dissolved waste catalyst, control the temperature at 70°C, and continue stirring for another 2.5 hours.

[0058] Weigh 125 kg of sodium carbonate and add it to the reactor within 1.5 hours. At the same time, slowly add 5 mol / L sodium hydroxide solution, control the pH to 9.5-10.5, control the temperature to 70°C, and continue stirring and precipitating for 14 hours.

[0059] Step 4, after the precipitation conversion is completed, the temperature is lowered to below 40°C, solid-liquid separation is performed, and centrifugal separation is performed, and the separated liquid is collected.

[0060] Step 5, after the solid is collected, it is washed in a washing tank, 150L of deionized water is added for stirring and washing, and then centrifuged; the washing is repeated 2-3 times, and 0.5-1% nitric acid solution can be appropriately added for neutralization in the last washing, and the solid material is washed until the pH is neutral.

[0061] Step 6: Put the solid material into the calcination tray and move it into the calcination furnace. Set the calcination temperature to 380°C, the heating rate to 12°C / min, keep 380°C for 140min, and cool it down to room temperature naturally before taking it out of the furnace.

[0062] Step 7, granulate the calcined powder into required specifications and sizes according to the needs of different application sites, and then measure and package it.

[0063] Performance Testing Gas chromatography.

[0064] The parameters are set as follows: CO flow rate: 30ml / min H2O temperature control (water vapor production): 30℃ Gas chromatograph: COL 140℃, TCD 150℃, DET 100℃ Specific process: 20.0000mg of sample is weighed accurately, mixed with 3ml of fine-grained quartz sand (specification 50 mesh) and loaded into the quartz tube; the loaded quartz tube is connected to the tubular furnace section of the gas phase online detection device, and the upper and lower interfaces are connected and fixed, and the seal is intact; start the gas chromatography preheating, and start the heating of the tubular furnace section for activation. The temperature is set to 4℃ / min, and it is maintained for 60min at 260℃. When the temperature rises to about 50℃, CO is introduced, and the activation stage is controlled at 20ml / min. At the same time, the H2O temperature controller controls the temperature at 30℃, and the outlet valve is opened, and the mixture is mixed with CO and enters the quartz tube to fully react with the material to be tested; the performance changes can be detected during the activation period, and the catalytic performance is detected online at the temperature control points of 140-180-220-260-300℃; after the activation is completed, the temperature is naturally reduced to 140℃, CO is adjusted to 30ml / min, the temperature is increased by 4℃ / min, and the detection is performed every 20℃, and the detection is performed to 260℃ (the detection temperature point can be appropriately adjusted according to the performance curve).

[0065] The activity and XRD of the copper-based catalysts after regeneration in Examples 1, 2, 3, and 4 were tested. The activity results are as follows: Figure 2 As mentioned above, the XRD test results are as follows Figure 3 The results show that compared with the waste copper-based catalyst ( Figure 2 Compared with A), the activity of the regenerated waste copper-based catalyst was significantly improved ( Figure 2 (B, C, D, E).

[0066] Figure 3 Figures D and E show that basic carbonates are generated by adding metal salt auxiliary materials and other auxiliary agent precursors. After activation, basic copper, zinc, and aluminum carbonates decompose to produce a decomposition reaction. After the catalyst is stabilized, its components are composed of Cu, ZnO, BaCO3, and Al2O3.

[0067] The regenerated copper-based catalyst of Example 3 was subjected to mapping detection. Figure 4 As shown, the components are evenly distributed after the copper-based catalyst is regenerated.

[0068] The regenerated copper-based catalyst in Example 4 was subjected to adsorption detection characterization and stability test, and the results are as follows Figure 5 and Figure 6 The results show that the activity of the regenerated copper-based catalyst decays by less than 10% after a test time of 100 hours, and the adsorption of the copper-based catalyst is significantly improved after regeneration, indicating that the adsorption performance and stability of the copper-based catalyst after regeneration are excellent, and the physical and chemical properties are significantly improved.

[0069] Therefore, the present invention adopts the above-mentioned method for regenerating a copper-based catalyst for hydrogen production by methanol cracking / reforming, takes waste copper-based catalyst as raw material, and prepares a highly active regenerated copper-based catalyst through regeneration procedures such as acid treatment and precipitation conversion, which not only improves the performance of the catalyst but also allows the catalyst to be recycled.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen, characterized in that: The following steps are involved: Step 1, crushing the waste copper-based catalyst: crushing and grinding the waste copper-based catalyst into powder; Step 2, acid treatment: using a mixed acid solution of an organic acid and an inorganic acid to acid-treat the powder in step 1 to obtain a mixed solution; Step 3, activation enhancement: adding metal salt auxiliary materials and additives to the mixed solution of step 2 to improve the comprehensive performance of the catalyst; Step 4, precipitation conversion: while step 3 is being carried out, a precipitant and a pH adjuster are added to convert the active substance; Step 5, separation: after the reaction of step 3 and step 4 is completed, solid-liquid separation is performed to obtain a solid catalyst crude material; Step 6, washing: washing the solid catalyst crude material with deionized water until the pH value is 6-8 to obtain a solid catalyst washing material; Step 7, calcination: calcining the solid catalyst wash material to obtain a finished powder regeneration catalyst; Step 8, granulation and packaging: the finished powder regenerated catalyst is further granulated to prepare granular catalysts of different sizes to obtain the regenerated finished copper-based catalyst, which is then packaged.

2. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 1, the powder particle size is 80-1000 mesh.

3. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 2, the organic acid is one or more of oxalic acid, citric acid, acetic acid, EDTA, glycolic acid, and formic acid; the inorganic acid is one or more of nitric acid and hydrochloric acid; and the molar ratio of the inorganic acid to the organic acid is inorganic acid: organic acid = 3-5:

1.

4. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 2, the ratio of powder to mixed acid solution is powder: mixed acid solution = 1 kg: 3-6 L, and the mixed acid solution contains 50-60 kg of acid per 300 L of deionized water.

5. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 2, the acid treatment conditions are a temperature of 50-90° C., stirring, and a reaction time of 10-24 h.

6. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 3, the precipitant is one or more of sodium carbonate and sodium bicarbonate, and the pH adjuster is one or more of sodium hydroxide and potassium hydroxide.

7. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 3, the reaction conditions are a temperature of 40-100° C. with stirring, a pH of 9.5-11, and a reaction time of 6-24 h.

8. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: In step 4, the metal salt auxiliary material is one or more nitrates containing manganese, zirconium, zinc, barium, copper, aluminum or magnesium; the auxiliary agent is one or more of P123, F127, PEG600; the molar ratio of Cu in the copper-based catalyst to the metal salt auxiliary material and the auxiliary agent is Cu: metal salt auxiliary material: auxiliary agent = 1: 0.01~0.08: 0~0.

015.

9. The method for regenerating a copper-based catalyst for methanol cracking / reforming to produce hydrogen according to claim 1, characterized in that: The calcination conditions in step 7 are to increase the temperature from room temperature to the calcination temperature at a heating rate of 8-15°C / min, keep the temperature for 120-200 minutes, and then cool down naturally; the calcination temperature is 320-420°C.

10. A copper-based catalyst for methanol cracking / reforming to produce hydrogen prepared by the regeneration method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Application method of waste copper based catalyst to preparing catalyst for preparing hydrogen from methanol

    CN102125851A

  • Method for preparing and synthetizing methanol catalyst from copper-based waste methanol catalyst recovered solution

    CN103480379A

  • Highly-effectively copper-based catalyst for decomposing methanol to produce hydrogen

    CN107824190A